PERILAKU PEMBELIAN AKIBAT PERUBAHAN KEBIJAKAN HARGA GO-FOOD SEBELUM DAN SESUDAH PANDEMI - Lianto, Fendy (Seminar Nasional Ilmu Terapan, 2024)
This study aims to explore how GoFood's pricing policy changes before and after the pandemic have influenced consumer purchasing behavior. The research uses a qualitative method with in-depth interviews conducted with 10 informants in Surabaya in 2023. Through these interviews, it was revealed that the changes in GoFood's pricing policy, especially the price increases that occurred after the pandemic, had a significant impact on consumer purchasing decisions.Consumers who previously tended to use GoFood services regularly due to the convenience and perceived affordability began to show changes in their behavior. After the pandemic, consumers became more selective in using the platform. They started considering alternative options, such as cooking at home or using services from other platforms that offered more competitive prices. The noticeable price increase after the pandemic was one of the main reasons behind this shift.On the other hand, the study's results also showed that many consumers remained loyal to GoFood despite the price increases. Factors such as the convenience of ordering food, the speed of delivery, and habits formed before the pandemic were the main reasons for their continued use of the service. Moreover, GoFood's service quality, including menu variety and reliable delivery, contributed to maintaining customer loyalty. This study recommends that GoFood regularly conducts surveys and interviews to understand the changing preferences and priorities of its customers. In addition, improving non-price aspects such as offering a more diverse menu, faster delivery times, and more innovative promotional offers could be an effective strategy for GoFood to respond to changes in consumer behavior. This way, GoFood can remain competitive in the increasingly crowdedpost-pandemic food delivery market.